Pengembangan Fortitude Questionnaire Versi Indonesia - Listyo Yuwanto; Gunadi Atmadji (Jurnal Ilmiah Psikologi MIND SET, 2017)
Fortitude is a strength or ability to manage stress consisting of self-appraisal, family appraisal, and support appraisal. Fortitude Questionnaire (FORQ) is a fortitude measurement tool developed by Pretorius and Heyns (2005), was consisted of 20 items that represented the dimensions of self-appraisal, family appraisal, and support appraisal. Based on literature studies, there was no Indonesian version of fortitude measuring tool. This limitation underlies the validation research of the Indonesian version of Fortitude Questionnaire. Validation includes testing the validity of internal structure and internal consistency reliability. Research respondents are 249 college students with an average age of 19 years. The results showed that the Indonesian version of Fortitude Questionnaire consists of 16 items with dimensions of self-appraisal, family appraisal, and support appraisal. Fortitude questionnaire Indonesian version met valid and reliable measurement method.